2019
DOI: 10.31937/akuntansi.v10i2.993
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ukuran KAP, Ukuran Perusahaan dan Manajemen Laba terhadap Integritas Laporan Keuangan

Abstract: This study aims to analyze the effect of KAP size, firm size and earnings management on the integrity of financial statements. The integrity of financial statements is the extent to which the financial statements presented indicate true and honest information. This study was taken because there are still contradictions from previous studies. This study uses secondary data. The population in this study is the consumer goods industry companies listed on the Indonesia Stock Exchange in 2012-2016. Determination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 1 publication
(1 reference statement)
3
3
0
6
Order By: Relevance
“…The following are the results of the partial significance"test: Source: Data processed Eviews 9.0, 2021 Based on the results of the partial test using Eviews 9.0 software for the earnings management variable (MNJ_LABA), it can be concluded that earnings management has an insignificant positive effect on the increase in the integrity of financial report. The results of this study support the research conducted by Lubis, Fujianti, & Amyulianthy (2018), that earnings management has no significant positive effect, which means that higher earnings management will affect the high integrity of financial report. These results indicate that earnings management is one of the methods used by stakeholders in the preparation of financial report as the financial report become a communication tool for internal parties to external parties aimed at maintaining good performance in the eyes of stakeholders and investors in order to strengthen stock prices (Priantinah, 2016).…”
Section: Common Effect Model Estimation Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The following are the results of the partial significance"test: Source: Data processed Eviews 9.0, 2021 Based on the results of the partial test using Eviews 9.0 software for the earnings management variable (MNJ_LABA), it can be concluded that earnings management has an insignificant positive effect on the increase in the integrity of financial report. The results of this study support the research conducted by Lubis, Fujianti, & Amyulianthy (2018), that earnings management has no significant positive effect, which means that higher earnings management will affect the high integrity of financial report. These results indicate that earnings management is one of the methods used by stakeholders in the preparation of financial report as the financial report become a communication tool for internal parties to external parties aimed at maintaining good performance in the eyes of stakeholders and investors in order to strengthen stock prices (Priantinah, 2016).…”
Section: Common Effect Model Estimation Resultssupporting
confidence: 86%
“…The results of the partial test using Eviews 9.0 software for the variable size of the public accounting firm (UK_KAP), it can be concluded that the size of the public accounting firm has a positive and insignificant effect on the integrity of financial report. The results of this study support the research conducted by Lubis, Fujianti, & Amyulianthy, (2018) and Qoyyimah, et al (2015) stating that the size of a public accounting firm has a positive and insignificant effect on the integrity of financial report. The small influence of the size of the public accounting firm on the integrity of financial report is because in its application, the big-four KAP or non-big-four KAP both have standards that are in accordance with the Professional Standards of Public Accountants (SPAP) at the time of auditing the company's financial report.…”
Section: Conclusion Limitations and Suggestionssupporting
confidence: 87%
See 1 more Smart Citation
“…Dengan semakin besar ukuran perusahaan maka akses informasi yang tersedia untuk publik akan semakin banyak, sehingga campur tangan dalam penyusunan pelaporan keuangan eksternal dapat bertujuan menguntungkan diri sendiri dan akan menurunkan integritas laporan keuangan. Hasil penelitian ini mendukung hasil penelitian terdahulu yang dilakukan oleh (Lubis, Fujianti, & Amyulianthy, 2019) dan (Pratika & Primasari, 2020) yang menyatakan bahwa ukuran perusahaan tidak berpengaruh terhadap integritas laporan keuangan. Hasil penelitian ini tidak sejalan dengan penelitian yang dilakukan oleh (Fauziah & Panggabean, 2019) menyatakan bahwa ukuran perusahaan berpengaruh positif terhadap integritas laporan keuangan dengan semakin besar ukuran perusahaan maka semakin meningkat integritas laporan keuangannya karena manajer cenderung lebih konservatif ketika memilih untuk mengurangi keuntungan tanpa adanya overstate atas nilai asetnya sehingga laporan keuangan yang dihasilkan akan reliable.…”
Section: Pengaruh Ukuran Perusahaan Terhadap Integritas Laporan Keuanganunclassified
“…Bangkitnya perusahaan-perusahaan besar menciptakan kebutuhan sebuah sistem informasi yang lebih kompleks, yang lebih sulit dilayani oleh akuntansi manajemen yang ada (Lubis, Fujianti, & Amyulianthy, 2019). Hal ini menimbulkan gagasan untuk menyempurnakan akuntansi manajemen, yang mampu memberikan informasi yang diperlukan bagi pengambilan keputusan.…”
Section: Metode Penelitianunclassified